(untitled) (Impetus, 2021)
A study is presented on the causes and effects of the violence experienced by fans who go to soccer stadiums in Mexico, since in the In recent years there has been a significant increase that affects the coexistence and enjoyment of society. A survey was applied on the causes and effects of violence to 400 fans who come to the stadiums of football and that they are over 18 years old. The results show that among the causes that originate violence are adopting negative behaviors of other countries by specific animation groups called bars and the sale of alcohol. On the other hand, acts of violence in soccer stadiums in Mexico are being more frequent, that they are not taking the preventive measures to prevent it and have stopped attend a game for fear of possible violent acts, that bars should be banned and that fans who engage in violent acts should be prohibited from entering to the stadiums and if necessary punish them with jail.